Approaches for enantioselective resolution of pharmaceuticals by miniaturised separation techniques with new chiral phases based on nanoparticles and monolithis. Issue 19 (29th August 2016) - Sierra, Isabel; Marina, Maria Luisa; Pérez‐Quintanilla, Damián; Morante‐Zarcero, Sonia; Silva, Mariana
Abstract : This article discusses new developments in the preparation of nanoparticles and monoliths with emphasis upon their application as the stationary and pseudo‐stationary phases for miniaturised liquid phase separation techniques, which have occurred in the last 10 years (from 2006 to the actuality). References included in this review represent current trends and state of the art in the application of these materials to the analysis, by EKC, CEC and miniaturised chromatography, of chiral compounds with environmental interest such as pharmaceuticals. Due to their extraordinary properties, columns prepared with these new chiral stationary or pseudo‐stationary phases, based on materials such as gold nanoparticles, metal‐organic frameworks, ordered mesoporous silicas, carbonaceous materials, polymeric‐based and silica‐based monoliths or molecularly imprinted materials, can usually show some improvements in the separation selectivity, column efficiency and chemical stability in comparison with conventional chiral columns available commercially.